Pengembalian Fungsi Pengawasan Pemilu Kepada Masyarakat Sebagai Wujud Penyelenggaraan Pemilu Yang Demokratis - Dinaka, Burhan Robith; Arsil, Fitra (UI Scholars Hub, 2023)
Elections as a means of implementing people's sovereignty which are held directly, publicly, freely, confidentially, honestly and fairly within the territory of the Unitary State of the Republic of Indonesia which are based on Pancasila and the 1945 Constitution of the Republic of Indonesia also mandate a model of election supervision through Bawaslu as the election organizing institution whose task is to observe, review, inspect and assess the election implementation process so that it runs in accordance with the provisions of applicable laws and regulations. The ongoing strengthening of positions, duties, functions and authority within Bawaslu has left a number of problems. On the other hand, active involvement in the role of the community as owners of sovereignty is also an inseparable part in the realization of holding democratic elections. This research aims to examine the urgency and model of election supervision carried out by the community. In studying this problem, this research uses qualitative research methods with research results in the form of prescriptive normative analysis. In this research, it was concluded that massive civil society participation in overseeing elections must continue to be pursued. One of them is by providing guarantees of the availability of funds obtained by each election monitoring actor to carry out their duties and functions as election observers. Meanwhile, Bawaslu can focus on enforcing election law. Burhan Robith Dinaka, University of Indonesia Fitra Arsil, University of Indonesia Keywords: electoral justice, electoral monitoring, electoral observation